Percutaneous Electrolysis in the Treatment of Lateral Epicondylalgia: A Single-Blind Randomized Controlled Trial. - Rodríguez-Huguet, Manuel; Góngora-Rodríguez, Jorge; Lomas-Vega, Rafael; Martín-Valero, Rocío; Díaz-Fernández, Ángeles; Obrero-Gaitán, Esteban; Ibáñez-Vera, Alfonso Javier; Rodríguez-Almagro, Daniel (MDPI, 2020)
Few studies have considered the effects of percutaneous electrolysis (PE) in the treatment of lateral epicondylalgia (LE). For this reason, the objective of this study was to compare the effects of PE with an evidence-based approach-trigger point dry needling (TDN)-in patients with LE. A randomized controlled trial was conducted in which 32 participants with LE were randomly assigned to two treatment groups, the PE group (n = 16) and the TDN group (n = 16). Both groups received four therapy sessions and an eccentric exercise program to be performed daily. The numerical pain rating scale (NPRS), pressure pain thresholds (PPT), quality of life, and range of motion were measured before treatment, at the end of treatment, and at one- and three-month follow-ups. Significant between-group mean differences were found after treatment for NPRS (p < 0.001) and flexion movement (p = 0.006). At one-month follow-up, significant mean differences between groups were found for NPRS (p < 0.001), PPT (p = 0.021), and flexion (p = 0.036). At three-months follow-up, significant mean differences between groups were found for NPRS (p < 0.001), PPT (p = 0.004), and flexion (p = 0.003). This study provides evidence that PE could be more effective than TDN for short- and medium-term improvement of pain and PPTs in LE when added to an eccentric exercise program.
Keywords: Epicondilitis - Fisioterapia; Elbow tendinopathy; Electrolysis; Lateral epicondyalgia; Tennis elbow; Physical therapy